The Influence of Leadership Style and HR Service on Performance Mediated by Organizational Commitment to Employees Regional Office of the Ministry of Law and Human Rights of North Sumatra - Rinaldi Muhammad Parlindungan; Yohny Anwar (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to test and analyze the influence of leadership style and HR service on organizational commitment, to test and analyze the influence of leadership style and HR service on employee performance. As well as to test and analyze the influence of leadership style and HR services on employee performance mediated by organizational commitment. The research method used in this study is a quantitative method. Data analysis using SMART PLS. The sample in this study is 56 respondents. The results of the study show that leadership style and HR service have a positive and significant effect on organizational commitment. Leadership style and HR service have a positive and significant effect on employee performance. As well as leadership style and HR service have a positive and significant effect on employee performance mediated by organizational commitment.